Using a virtual patient system for the teaching of pharmaceutical care. Issue 9 (September 2015) - Menendez, Elisa; Balisa-Rocha, Blície; Jabbur-Lopes, Monique; Costa, Wanderson; Nascimento, José Rafael; Dósea, Marcos; Silva, Leila; Lyra Junior, Divaldo
Highlights Virtual patient tools improve student's communication and clinical skills. Students experienced a similar reality to the one they will find in the future. The tutors had an important role guiding the students and providing feedback. Students were satisfied with PharmaVP as a complementary technique of learning.